2017
DOI: 10.1097/npt.0000000000000180
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation and Neuroplasticity: Role in Rehabilitation After Stroke

Abstract: Background and Purpose In many neurologic diagnoses significant inter-individual variability exits in the outcomes of rehabilitation. One factor that may impact response to rehabilitation interventions is genetic variation. Genetic variation refers to the presence of differences in the DNA sequence among individuals in a population. Genetic polymorphisms are variations that occur relatively commonly and, while not disease-causing, can impact the function of biological systems. The purpose of this article is to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 100 publications
(101 reference statements)
0
34
0
2
Order By: Relevance
“…Researchers and therapists are still looking for a new possibility of impact of the neuronal system; it will contribute in the future to the functional progress and usage capacity of the mechanisms of neuronal plasticity in the case of his damage [ 108 ].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers and therapists are still looking for a new possibility of impact of the neuronal system; it will contribute in the future to the functional progress and usage capacity of the mechanisms of neuronal plasticity in the case of his damage [ 108 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another factor that may be a source of a lot of variation between studies is the genetics of the individuals involved. Research suggests that polymorphisms in genes such as BDNF and apolipoprotein E may influence stroke recovery, and specifically may interact with treatments (Stewart and Cramer, 2017 ). Genetic polymorphisms potentially impacting dopaminergic response exist at varying rates in the population notably for COMT, DAT, D 1 R, D 2 R and D 3 R (Pearson-Fuhrhop et al, 2013 ).…”
Section: Clinical Evidence For the Use Of Da-enhancing Drugs In Motormentioning
confidence: 99%
“…In speech and language research, several functional and structural neuroimaging studies have shown that both residual and new neural mechanisms can be recruited in the recovery process after stroke [e.g., see ( 67 , 68 )]. Genetic ( 69 ) and biological ( 70 ) factors also likely contribute to recovery across domains. The role of neuroplasticity in speech and language recovery is however not fully understood yet ( 71 ).…”
Section: Discussionmentioning
confidence: 99%